2004
DOI: 10.1093/protein/gzh090
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial exploration of the catalytic site of a drug-resistant dihydrofolate reductase: creating alternative functional configurations

Abstract: We have applied a global approach to enzyme active site exploration, where multiple mutations were introduced combinatorially at the active site of Type II R67 dihydrofolate reductase (R67 DHFR), creating numerous new active site environments within a constant framework. By this approach, we combinatorially modified all 16 principal amino acids that constitute the active site of this enzyme. This approach is fundamentally different from active site point mutation in that the native active site context is no lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 33 publications
2
69
0
Order By: Relevance
“…Bacterial extracts were prepared as described by Schimtzer et al (48). 1-ml columns of glutathione-Sepharose 4B (GE Healthcare) were prepared according to the manufacturer's protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial extracts were prepared as described by Schimtzer et al (48). 1-ml columns of glutathione-Sepharose 4B (GE Healthcare) were prepared according to the manufacturer's protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Potentially, molecular dynamic simulations can provide further insight into the feasibility of this potential catalytic mechanism. An additional constraint on the possible catalytic mechanism is derived from the recent combinatorial studies reported by Schmitzer et al (61) In particular, they demonstrated that co-evolution of residues 66-69 in the active site could produce variants with kinetic behavior that are generally similar to that observed for the native enzyme. The wt sequence is V66-Q67-I68-Y69 while the active mutant sequences are S66-K67-I68-H69 or I66-N67-R68-Y69 or G66-E67-L68-Y69.…”
Section: Catalytic Mechanismmentioning
confidence: 99%
“…[22] A wide variety of structural and kinetic data also support this model, [23][24][25][26][27] including directed evolution experiments where the four active-site residues of R67-DHFR can be substituted by a variety of other residues. [28] Since R67-DHFR is a homotetramer with a single active site pore, this scenario results in sixteen changes per active site; yet, the mutants are as active as the wild-type R67-DHFR. Such tolerance is typical of poorly evolved enzymes.…”
mentioning
confidence: 99%
“…Such tolerance is typical of poorly evolved enzymes. [18,28] To improve R67-DHFR function further, gene duplication or quadruplication, followed by divergence of individual gene copies needs to occur. Such studies with modified enzymes where the 222 symmetry is broken [29] are underway.…”
mentioning
confidence: 99%